1998
DOI: 10.1007/s002770050364
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction after bone marrow transplantation: Increase of soluble thrombomodulin and PAI-1 in patients with multiple transplant-related complications

Abstract: Multiple transplant-related complications (MTRC) represent a severe condition after bone marrow transplantation (BMT) and are supposed to reflect systemic endothelial damage. Soluble thrombomodulin (sTM) and plasminogen activator inhibitor type-1 (PAI-1) were investigated as markers of endothelial dysfunction in 35 patients after autologous or allogeneic BMT and compared with the occurrence of the typical complications sepsis, veno-occlusive disease of the liver (VOD), graft-versus-host disease (GVHD), and cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 14 publications
3
80
2
1
Order By: Relevance
“…37 Soluble thrombomodulin and plasminogen activator type 1, markers of endothelial injury are elevated in persons with capillary leak syndrome and other complications of transplantation, such as GVHD, hepatic veno-occlusive disease and sepsis. 38 Recombinant human soluble thrombomodulin has also been shown to ameliorate the vascular leak manifestations of ES. 39 As more biomarkers of GVHD are identified, 40 it may be possible to better determine how to distinguish ES from GVHD and whether they are are different or identical processes.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…37 Soluble thrombomodulin and plasminogen activator type 1, markers of endothelial injury are elevated in persons with capillary leak syndrome and other complications of transplantation, such as GVHD, hepatic veno-occlusive disease and sepsis. 38 Recombinant human soluble thrombomodulin has also been shown to ameliorate the vascular leak manifestations of ES. 39 As more biomarkers of GVHD are identified, 40 it may be possible to better determine how to distinguish ES from GVHD and whether they are are different or identical processes.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…At the time of engraftment or at the onset of GVHD, VWF and TM levels were significantly increased with respect to the baseline, especially in patients with acute GVHD grades II-IV, suggesting that ECs could be injured. Nu¨rnberg et al 22 analysed levels of plasminogen activator inhibitor type 1 and TM and demonstrated that the increases in both markers correlated with the number of vascular complications (VOD, sepsis, capillary leak syndrome) and to a lesser degree with GVHD. Takatsura et al 23 did not observe any impact of TBI on VWF and TM levels.…”
Section: Soluble Markers and Adhesion Moleculesmentioning
confidence: 99%
“…Plt activation is also characteristic for generalized endothelial injury, exposing phospholipid surfaces to generate thrombin, and secrete inflammatory mediators, also after SCT. [10][11][12] Some studies have focused on coagulation and fibrinolytic activities during SCT. In a study of mainly autologous transplant patients, increased coagulation activity was reported during conditioning therapy, whereas fibrinolytic mechanisms were shown to be triggered later.…”
Section: Introductionmentioning
confidence: 99%